(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
The light industry plays a crucial role in the world economy and includes the production of textiles, fashion and clothing. Over the years, innovative technologies have had a significant impact on this sector, revolutionizing production processes, sustainability and product customization. This article explores the impact of innovative technologies in light industry, focusing on their role in productivity, sustainability and product development